Humidification dehumidification desalination system using parabolic trough solar air collector. (22nd January 2015) - Al-Sulaiman, Fahad A.; Zubair, M. Ifras; Atif, Maimoon; Gandhidasan, Palanichamy; Al-Dini, Salem A.; Antar, Mohamed A.
Abstract: This paper deals with a detailed thermodynamic analysis to assess the performance of an HDH system with an integrated parabolic trough solar collector (PTSC). The HDH system considered is an open air, open water, air heated system that uses a PTSC as an air heater. Two different configurations were considered of the HDH system. In the first configuration, the solar air heater was placed before the humidifier whereas in the second configuration the solar air heater was placed between the humidifier and the dehumidifier. The current study revealed that PTSCs are well suited for air heated HDH systems for high radiation location, such as Dhahran, Saudi Arabia. The comparison between the two HDH configurations demonstrates that the gained output ratio (GOR) of the first configuration is, on average, about 1.5 whereas for the second configuration the GOR increases up to an average value of 4.7. The study demonstrates that the HDH configuration with the air heater placed between the humidifier and the dehumidifier has a better performance and a higher productivity. Highlights: Thermodynamic analysis of an HDH system driven by a parabolic trough solar collector was conducted. The first configuration reveals a GOR of 1.5 while the second configuration reveals a GOR of 4.7. Effective heating of the HDH system was obtained through parabolic trough solar collector.